Moderators of changes in smoking, drinking and quitting behaviour associated with the first COVID‐19 lockdown in England. (25th August 2021) - Jackson, Sarah E.; Beard, Emma; Angus, Colin; Field, Matt; Brown, Jamie
Abstract: Aim: To estimate changes in smoking, drinking and quitting behaviour from before to during the first COVID‐19 lockdown in England, and whether changes differed by age, sex or social grade. Design: Representative cross‐sectional surveys of adults, collected monthly between August 2018 and July 2020. Setting: England. Participants: A total of 36 980 adults (≥ 18 years). Measurements: Independent variables were survey month (pre‐lockdown: August–February versus lockdown months: April–July) and year (pandemic: 2019/20 versus comparator: 2018/19). Smoking outcomes were smoking prevalence, cessation, quit attempts, quit success and use of evidence‐based or remote cessation support. Drinking outcomes were high‐risk drinking prevalence, alcohol reduction attempts and use of evidence‐based or remote support. Moderators were age, sex and occupational social grade (ABC1 = more advantaged/C2DE = less advantaged). Findings: Relative to changes during the same time period in 2018/19, lockdown was associated with significant increases in smoking prevalence [+24.7% in 2019/20 versus 0.0% in 2018/19, adjusted odds ratio (aOR) = 1.35, 95% confidence interval (CI) = 1.12–1.63] and quit attempts (+39.9 versus –22.2%, aOR = 2.48, 95% CI = 1.76–3.50) among 18–34‐year‐olds, but not older groups. Increases in cessation (+156.4 versus –12.5%, aOR = 3.08, 95% CI = 1.86–5.09) and the success rate of quit attempts (+99.2 versus +0.8%, aOR = 2.29, 95% CI = 1.31–3.98) were also observed, and did not differ significantly by age, sex or social grade. Lockdown was associated with a significant increase in high‐risk drinking prevalence among all socio‐demographic groups (+39.5 versus –7.8%, aOR = 1.80, 95% CI = 1.64–1.98), with particularly high increases among women (aOR = 2.17, 95% CI = 1.87–2.53) and social grades C2DE (aOR = 2.34, 95% CI = 2.00–2.74). Alcohol reduction attempts increased significantly among high‐risk drinkers from social grades ABC1 (aOR = 2.31, 95% CI = 1.78–3.00) but not C2DE (aOR = 1.25, 95% CI = 0.83–1.88). There were few significant changes in use of support for smoking cessation or alcohol reduction, although samples were small. Conclusions: In England, the first COVID‐19 lockdown was associated with increased smoking prevalence among younger adults and increased high‐risk drinking prevalence among all adults. Smoking cessation activity also increased: more younger smokers made quit attempts during lockdown and more smokers quit successfully. Socio‐economic disparities in drinking behaviour were evident: high‐risk drinking increased by more among women and those from less advantaged social grades (C2DE), but the rate of reduction attempts increased only among the more advantaged social grades (ABC1).